Education and observation of the 2023 hybrid solar eclipse in Southwest Papua - Endra Putra Raharja; Muhammad Faizin; Yudhiakto Pramudya; N. Nurinaya; Muhklas Triono; Surya Putra Raharja (Journal of Community Service and Empowerment, 2024)
On April 20, 2023, the Southwest Papua region was the areas crossed by a hybrid solar eclipse. This outreach aims to enhance the community's understanding and awareness regarding the safety of solar eclipse observation by conducting observations at several locations in Southwest Papua. The Solar Gehana Education and Observation Program was successfully implemented in 6 Regencies/Cities in Southwest Papua. This activity was carried out using mini-lectures, pinhole training, and joint eclipse observations. In general, this program can increase public understanding and awareness regarding the safety of observing solar eclipses, with the training participants' response score being 79.92% in the good category. Apart from that, this program has succeeded in touching and opening people's insight into this fascinating natural phenomenon through widespread publication in the mass media, both regional and national.